Teacher professional development as a mechanism to advance education for sustainable development (ESD) integration in Namibia: a senior primary English language case study - Shangheta, Miryam Keshityeni (Rhodes University, Faculty of Education, Department of Environmental Learning Research Centre)
Namibia is a signatory to the Sustainable Development Goals of Agenda 2030 and responds to the United Nations Decade of Education for Sustainable Development by incorporating Education for Sustainable Development (ESD) into its education curriculum and policies. In 2020, Namibia launched its National Environmental Education and Education for Sustainable Development Policy. Despite these policy commitments, research indicates that most teachers continue to struggle with integrating ESD into their teaching practices. The integration of ESD in English language teaching classrooms is no exception. This qualitative case study is an attempt to understand how a Teacher Professional Development programme named Teach for ESD offered by NaDEET, a non-governmental organisation in Namibia, aided three Senior Primary Phase English Language teachers to integrate ESD into their teaching practice. The study also aims to unveil the teaching practice of the selected English Language teachers in the Otjozondjupa region who participated in the Teach for ESD programme. Data was gathered using semi-structured interviews (three interviews per teacher), document review, and lesson observation (one per teacher). Theoretically, the study is framed by socio-cultural learning theory after the work of Lev Vygotsky, supplemented by Mavhunga and Rollnick's (2013) account of Topic Specific Pedagogical Content Knowledge (TSPCK). The qualitative data was analysed inductively to identify themes and sub-themes relevant to the research questions. The study findings might be of value to NaDEET as they implement future TPD courses in ESD, and they may also be of interest to English Language Teaching stakeholders as Namibia implements the EE and ESD Policy in the national school curriculum. The findings showed that the English Language teachers need ESD training; ESD-oriented teaching and learning materials; continuing support for monitoring and evaluation of their ESD practices; and more time allocated to English Language teaching in the timetable so that the environmental / sustainability content can be explored in more depth alongside the development of English Language skills. The study recommends that further research be conducted into effective ways of teaching English Language skills through environmental themes (developing Pedagogical Content Knowledge); and exploring up-scalable models of teacher professional development so that more English Language teachers can receive ESD training.
Keywords: Career development; Teachers In-service training; Education for sustainable development; English language-- Study and teaching-- Namibia; Pedagogical content knowledge